(untitled) (International Journal of Food and Nutritional Sciences, 2022)
With the passing of time, every country’s age structure of population passes through different stages. This age structure transition opens opportunities for demographic dividend. This opportunity comes in the middle stage of demographic change where the population pyramid indicates that the share of youth or working-age people is large in the total population and the dependency ratio becomes low. If a country engages this section of the population in a productive way, this can raise per capita income and higher the living standard of the people. It has been seen that youth are facing problems to get working opportunities in the formal economy due to inadequate skills, training and education. If this continues and youth are not absorbed productively in the formal economy then this demographic dividend will turn into a demographic nightmare. To get the benefits of this large share of the working age population, the government must come up with proper plans and policies to honing them so that they can cope up with the changing demand of the global market.